2017
DOI: 10.1159/000478104
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Realization and Inventory Size: Kannada and Malayalam Alveolar/Retroflex Laterals and /ɻ/

Abstract: This study examines formant and spectral moment data for the apical and retroflex lateral sounds /l ɭ/ of the Dravidian languages Kannada and Malayalam, together with the rhotic /ɻ/ of Malayalam. Data are presented for 10 male speakers of each language. We find that the first spectral moment is lower for retroflex laterals than for alveolar laterals, and lower for the rhotic /ɻ/ of Malayalam than for the retroflex lateral in the same language. Differences emerge when the retroflex lateral of Kannada is compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 27 publications
2
15
1
Order By: Relevance
“…The lower F2 in /í/ is the opposite to the finding for F2 in Tamil. The duration of /í/ in Malayalam is also reported to be shorter than that of /l/ (Punnoose 2011;Tabain & Kochetov 2018), which is consistent with the finding of duration for Tamil. As for Kannada, descriptive phonetic accounts disagree on the exact place of the articulation of its non-retroflex coronal lateral /l/: some describe it as 'dental' (Bright 1958), others as 'alveolar' (Upadhyaya 1972), but they unanimously characterize /í/ as retroflex, with some noting its subapical articulation.…”
Section: Acoustic and Phonotactic Characteristics Of Retroflex Latera...supporting
confidence: 80%
See 2 more Smart Citations
“…The lower F2 in /í/ is the opposite to the finding for F2 in Tamil. The duration of /í/ in Malayalam is also reported to be shorter than that of /l/ (Punnoose 2011;Tabain & Kochetov 2018), which is consistent with the finding of duration for Tamil. As for Kannada, descriptive phonetic accounts disagree on the exact place of the articulation of its non-retroflex coronal lateral /l/: some describe it as 'dental' (Bright 1958), others as 'alveolar' (Upadhyaya 1972), but they unanimously characterize /í/ as retroflex, with some noting its subapical articulation.…”
Section: Acoustic and Phonotactic Characteristics Of Retroflex Latera...supporting
confidence: 80%
“…While the Tamil /í/ has sublingual articulation with palatal constriction, /í/ in Malayalam has a considerable tongue root retraction and a substantial tongue blade raising and retraction (Scobbie et al 2013). Acoustic studies show a higher F1, lower F2 and lower F3 in /í/ than in /l/ (Punnoose 2011;Punnoose et al 2013;Tabain & Kochetov 2018). The lower F2 in /í/ is the opposite to the finding for F2 in Tamil.…”
Section: Acoustic and Phonotactic Characteristics Of Retroflex Latera...mentioning
confidence: 96%
See 1 more Smart Citation
“…Differences in phoneme distribution have been reported for Hindi [14], Kannada [15] and several other Indian languages [16]. Further, acoustic properties of Indian phonemes are also markedly different vis-à-vis English, as reported by Kochetov and Sreedevi [17] and Tabain and Kochetov [18]. Such differences may be a source of a marked difference in LTASS for Indian languages relative to English.…”
Section: Long Term Average Speech Spectrummentioning
confidence: 76%
“…However, the F3 model which has significantly lower F3 for laterals in pre-pausal position and before consonants. Lowered F3 is a property of retroflex laterals, as Tabain et al (2016) and Tabain and Kochetov (2018) have shown for languages retroflex laterals that contrast with other coronal-laterals. Thus, the models suggests that the retroflex realization of the Korean lateral is more wide-spread than suggested in Hwang et al (2019), occurring not only word-finally but in word-internal syllable-final positions, as well.…”
Section: Tap Lateral Percent Tapsmentioning
confidence: 86%